2012
DOI: 10.1590/s0080-62342012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Como os trabalhadores de um Centro Obstétrico justificam a utilização de práticas prejudiciais ao parto normal

Abstract: Este estudo busca entender as justificativas dos trabalhadores de um Centro Obstétrico do Sul do Brasil para a utilização de práticas do parto normal consideradas prejudiciais pela Organização Mundial da Saúde. A pesquisa é do tipo exploratória, desenvolvida em julho de 2009, por meio de entrevista com 23 trabalhadores. Na análise, houve a conformação de três núcleos temáticos: Ações e condutas na dependência do trabalhador de saúde; Práticas rotineiras como facilitadoras do trabalho e Restrição da participaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 14 publications
0
13
0
15
Order By: Relevance
“…Prenatal care provides access to critical information for the autonomy of women and supports decision making related to childbirth (11,17,(20)(21) . Group activities contribute to the safety and autonomy of the couple, and generate changes in attitudes and behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prenatal care provides access to critical information for the autonomy of women and supports decision making related to childbirth (11,17,(20)(21) . Group activities contribute to the safety and autonomy of the couple, and generate changes in attitudes and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that the professionals who are present during delivery are responsible for indicating and performing certain practices since they are qualified to assess the need for interventions and prevent complications. However, standardisation or authoritative imposition and not requesting the informed consent of the women subjugates them and hinders their emancipation as an active agent of the parturition process (19,21,23) . It was also observed that the care practices that intensify the sensation of pain in labour negatively interfere in the autonomy of Brazilian women (17-18, 20, 23, 25-26, 29-30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11,21,22,23) O Programa de Humanização no Pré-natal e Nascimento (PHPN), de 01/06/2000 visa, dentre outras coisas, ampliar o financiamento de cursos de especialização em enfermagem obstetrícia. (3,6,24,25) Além dos objetivos citados, o PHPN ambiciona reduzir as altas taxas de morbimortalidade materna e perinatal e ampliar o acesso ao pré-natal. (26) Com o objetivo de possibilitar um atendimento qualificado, fundamentado nos princípios da humanização à assistência, foi criado em 2010, pelo MS, a Portaria nº 4.279/GM/MS, a Rede Cegonha.…”
Section: Categoria 1: Evolução Da Enfermagem Obstétrica E Da Humanizaunclassified
“…De acordo com a Organização Mundial de Saúde (OMS), a gestação de baixo risco pode ser acompanhada por um enfermeiro obstétrico, sendo este também apropriado para tal função. (6,7) Ao pesquisarmos sobre a humanização do parto, notamos que esta temática é bastante abordada na literatura, porém a atuação e contribuição da equipe de enfermagem neste processo ainda são pouco descritas. Esse fato motivou uma revisão de literatura com intuito de buscar maior notoriedade e autonomia para a enfermagem obstétrica a atuação das enfermeiras quanto a humanização do parto.…”
Section: Introductionunclassified